Predictors of mitral annulus enlargement? A real-time three-dimensional transesophageal study. (1st November 2018) - Boilève, V.; Dreyfus, J.; Attias, D.; Scheuble, A.; Codogno, I.; Brochet, E.; Vahanian, A.; Messika-Zeitoun, D.
Abstract: Background: Mitral annulus (MA) enlargement can be observed in various cardiac conditions but respective influence of left atrial (LA) and left ventricle (LV) size remained unclear. Methods: In 120 patients who underwent a clinically indicated 3D-transesophageal-echocardiography, 30 atrial fibrillation (AF), 30 secondary mitral regurgitation (SMR), 30 primary myxomatous mitral regurgitation (PMR) and 30 mitral stenosis (MS), we evaluated the association between MA area (MA-area) and LA volume (LAvol) measured using the biplane area-length method, end-diastolic (LVEDV) and end-systolic (LVESV) volumes measured using the biplane Simpson method. MA-area was measured based on 3D datasets using QLab10. Results: MA-area was correlated to LVEDV (r = 0.42, p < 0.0001), LVESV (r = 0.29, p = 0.001) but more markedly to LAvol (r = 0.62, p < 0.0001). Correlation between MA-area and LAvol was sustained in all subsets whereas MA-area was not correlated to LVEDV and LVESV in patients with SMR and with PMR (all p > 0.10). In multivariate analysis main predictors of MA-area were LAvol (p < 0.0001) and myxomatous etiology of MR (p = 0.0003) followed by LVEDV (p = 0.006) and LVESV (p = 0.02). Conclusion: In a population of patients with a wide range of LA/LV size related to various conditions, LA volume and myxomatous MR etiology appeared as main predictors of MA size whereas LV size had a more modest influence. Highlights: The mitral annulus is at the interface of the left ventricle and of the left atrium. Respective influence of left atrial and left ventricle size remained is unclear. We assessed mitral annulus area using on 3D-TEE in 4 subsets. Left atrium volume was the stronger predictor of the of the mitral annulus enlargement.